2020
DOI: 10.1073/pnas.2016921117
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial vulnerabilities of human decision-making

Abstract: Adversarial examples are carefully crafted input patterns that are surprisingly poorly classified by artificial and/or natural neural networks. Here we examine adversarial vulnerabilities in the processes responsible for learning and choice in humans. Building upon recent recurrent neural network models of choice processes, we propose a general framework for generating adversarial opponents that can shape the choices of individuals in particular decision-making tasks toward the behavioral patterns desired by t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…In cognitive neuroscience, another approach to this problem is to use behavioural experimental tools to explain the model’s behaviour [6,10]. One way to carry out this task is by examining the different experimental settings that make the model fail, known as adversarial examples, [24], which has a long tradition in cognitive psychology, from the use of visual illusions to study perception to the characterisation of biases in decision making [43]. Another method is to train many models with different goals, and to examine which models best describe human behaviour [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cognitive neuroscience, another approach to this problem is to use behavioural experimental tools to explain the model’s behaviour [6,10]. One way to carry out this task is by examining the different experimental settings that make the model fail, known as adversarial examples, [24], which has a long tradition in cognitive psychology, from the use of visual illusions to study perception to the characterisation of biases in decision making [43]. Another method is to train many models with different goals, and to examine which models best describe human behaviour [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers used different approaches to overcome this problem. One approach was to train many different models with different goals, and examine how they perform in predicting human behaviour, thus controlling for the model’s goal [23], and another approach was to use adversarial examples that meant misleading a model and thus gaining insights on its operations [24]. We suggest another direction, which is to use tools from cognitive neuroscience, the same explicit cognitive models described above, to characterise and explain the operations of such a data-driven black box model.…”
Section: Introductionmentioning
confidence: 99%
“…This privacy issue can be further extended to the sport business space Dezfouli et al ( 2020 ) have shown how AI can be designed to manipulate human behaviour. Algorithms learned from humans' responses who were participating in controlled experiments.…”
Section: The Future Of Ai In Sportmentioning
confidence: 99%
“…The RL agent's goal is to intervene in its environment of human users to learn an optimal policy maximizing the accumulation of designer-specified rewards (e.g., clicks). Although platforms have only recently begun to apply RL to interact with and control digital environments of human users, researchers have demonstrated empirically that RL agents can induce humans to exhibit a variety of "target behaviors" selected for by algorithm designers 64 . A growing literature now details how RL-based systems can fail-often due to poorly specified reward functions-and how these failures may have social consequences 65 .…”
Section: Academic Data Science Research In the Realm Of Behavior Modificationmentioning
confidence: 99%